PENGARUH FASILITAS DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN PADA BANK SUMUT-MEDAN - Bakhtiar Bakhtiat (Universitas Islam Islam Sumatera Utara, 2018)
This paper is to discuss about the influence of work facilities and work environment to employees’ work spirit at the company namely Sumatera Utara Bank (PT. SUMUT Bank) Medan. This research is a quantitative research and employing questionnaire as instrument in data collection. A number of samples are 30 persons who are employees of the Bank, and are 10 % of the population (300 persons). The phenomenon in this research indicates that inadequate work facility and work environment can decrease employee’s morale or work spirit, and hence, lacking of productivity, ineffective and less achievement. The purpose of this study is to determine the effect of work facilities and work environment partially and simultaneously to employees’ morale or employees’ work spirit at PT. SUMUT Bank-Medan. The data analysis is using statistical approach such as multiple linear regression, t test, f test and determinant coefficient which are processed by using SPSS Version 20. The research result shows that multiple linear regression analysis obtained equation Y = 14,644 + 0,049 X1 + 0,640 X2. While, t test for work facility to employees’ work spirit is obtained equal to 0,021. This means that work facilities on employees’ work spirit is not significant, whereas, t test for work environment to employee’sspirit is obtained equal to 2,616. It means that the work environment to employees’ spirit is significant. The calculation of F test which is 4.217 indicating that work facilities and work environment give a positive and significant effect on employees’work spirit.